Self-esteem, anxiety and coping strategies to manage stress in ice hockey - Kaplánová, A. (Acta Gymnica, 2019)
Background: Sweating, increased heart rate, fidgeting, worrying thoughts and fear of failure are typical symptoms of an inability to manage stress in an important moment of match. Thus, there is well-founded need for psychological training that can help ice hockey players to control their emotions in stressful situations.